Concepts of law in the sciences, legal studies, and theology - Welker, Michael; Etzelmüller, Gregor (Religion in philosophy and theology, 2013)
This volume documents the results of an international, interdisciplinary exchange between legal scholars, theologians, scientists, and philosophers. During the course of several years, these thinkers explored analogies and differences between concepts of law in various academic disciplines, probing the sustainability of an interdisciplinary concept of law. While inspired by objectives of the natural law debate, the contributions nonetheless assume that a dialogue between theology and philosophy is not sufficient to forge both a critical and constructive association of "reason and religion." The contributors pursue a concept of law which is viable in multidisciplinary as well as international regard and, while drawing on the goals of the natural law debate, leaves its shortcomings behind.
Literaturangaben
Keywords: Aufsatzsammlung; Gesetz; Naturrecht